Innovative Utilization of Agricultural Waste for Sustainable Bio-Based Materials Development - Aisah, Intan Nur; Rahayu, Puput (SEAMEO BIOTROP, 2026)
Agricultural waste poses serious environmental challenges while offering untapped opportunities for bio-based innovation. This aim study is to evaluate an integrated process for converting agricultural residues (rice husks, corn cobs, and sugarcane bagasse) into sustainable bio-based composites. We applied pyrolysis (450–500 °C), biocomposite synthesis, and green-chemistry techniques to produce and characterize novel biomass-derived materials. The resulting composites exhibited high thermal stability (≈280 °C) and tensile strength (15–28 MPa), highlighting their potential as alternatives to petroleum-based plastics. This approach also reduced open burning and carbon emissions by about 35%, supporting biodiversity, bioenergy development, and SDG 12 (responsible consumption and production). These findings demonstrate a viable pathway for valorizing agricultural waste in a circular bio-based economy.